Предмет: Математика, автор: san7226

упростите выражение
 \frac{ \sqrt{48} -  \sqrt{3}( \sqrt{12} -  \sqrt{3})    }{ \sqrt{3} }

Ответы

Автор ответа: nafanya2014
2

\sqrt{48}=\sqrt{16\cdot 3}  =4\sqrt{3} \\\\\sqrt{12}=\sqrt{4\cdot 3}  =2\sqrt{3} \\\\\frac{\sqrt{48}-\sqrt{3}(\sqrt{12}-\sqrt{3})    }{\sqrt{3} } =\frac{4\sqrt{3}-\sqrt{3}(2\sqrt{3}-\sqrt{3})    }{\sqrt{3} } =\frac{\sqrt{3}(4-2\sqrt{3}+\sqrt{3} )}{\sqrt{3}} =4-\sqrt{3}


san7226: спасибо
nafanya2014: ))
Похожие вопросы
Предмет: Английский язык, автор: mariamkhachatr1
Предмет: Русский язык, автор: vikavip20